Cartas de Padres e Irmãos que andam por diversas partes da Índia (1541)
This 16th-century Jesuit correspondence, dating from 1545 to 1560, comprises a collection of transcribed letters and marginal annotations originating from Portuguese India, Malacca, Cochin, Goa, Japan, and the Persian Gulf. The documents detail missionary activities undertaken by members of the Society of Jesus, including key figures such as Father Mestre Francisco de Xavier, Father João de Beira, Father Gaspar, and Brother Melchior de Morais. Central themes include evangelisation efforts among local populations in India, Japan (notably Bungo and Yamaguchi), Socotora, and the Maluku Islands; reports on conversions, baptisms, and the establishment of Christian communities; and observations on indigenous religious practices, social structures, and cultural customs. The texts describe political dynamics involving local rulers, including the King of Supaa and the King of Maluco, some of whom expressed interest in converting to Christianity. Accounts of spiritual discipline, linguistic acquisition, interreligious conflict—particularly with Muslim authorities on Socotora—and the destruction of Hindu temples (*pagodes*) are recurrent. The correspondence also records logistical challenges, such as shortages of priests, difficulties in travel and communication across maritime networks, and appeals for additional personnel and financial support. Written primarily in Portuguese with transliterated names and terms preserved, these documents reflect the colonial ecclesiastical context of early modern Iberian expansion and provide critical insights into cross-cultural encounters, religious conversion, and the global reach of Catholic missionary enterprise during the 16th century.
Keywords: Beira; Evangelisation Efforts in Japan and Malacca; Gaspar; Jesuit Figures: Xavier; Jesuit Missionary Correspondence; Melchior; Portuguese India and Asian Trade Routes; Royal Library Mark; Scribe Indicators; Spiritual Discipline and Linguistic Challenges; Spiritual Exercises; Transcription; Various Parts of India; th-Century Jesuit Missionary Correspondence